Effect of elimination of diseases on expectation of life in Bangladesh - Aziza Sultana Rosy Sarkar; Md Nurul Islam (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - The purpose of this paper is to investigate the trend of life expectancy in Bangladesh and find the effect of eliminating the causes of diseases on life expectancy statistics. Design/methodology/approach - Data consisted of 1,530 deaths in 2000, 1,582 deaths in 2004 and 1,514 deaths in 2008 that were collected from the Health and Demographic Surveillance System of International Centre for Diarrheal Disease Research, Bangladesh. Trends in life expectancy after eliminating the cause of diseases were examined by a Single Decrement Life table. Findings - The expectation of life for both male and female presented differing patterns. Results showed that life expectancies were greatly reduced in the presence of all groups of non-communicable diseases (NCDs) in the community, whilst life expectancies were significantly improved if all NCDs within all disease groups were completely eliminated. The life expectancies in the presence of NCDs showed lowest expected years among all the present diseases groups and the life expectancies eliminating NCDs showed highest expected years among all the eliminating diseases groups. The results indicated that 10.99 years of life would be added to life expectancy at birth for the male population and 8.82 years for the female population in 2008 if NCDs were eliminated. Originality/value - The findings of this study provide useful information which could contribute to a more effective allocation of targeted funding for developing public health programs. Lowering mortality by eliminating major groups of diseases results in higher life expectancy ratings. Specifically, the relative impacts of eliminating cardiovascular diseases and respiratory diseases, as compared with eliminating neoplasms.